2020
DOI: 10.12775/jpm.2019.011
|View full text |Cite
|
Sign up to set email alerts
|

Organizational outcomes of corporate volunteering: the qualitative study

Abstract: The aim of this paper is to identify benefits of corporate volunteer programs gained on employee behaviors' side. Specifically, the following research question is posed: what benefits of corporate volunteer projects can be observed by employees participating in them?Methodology/approach: The paper is based on a qualitative study conducted in the form of semistructured in-depth individual interviews with employees participating in volunteer programs. Findings:The study shows that corporate volunteering leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…We show that participation in CV moderates: (1) the link between experienced positive relationships with peers and employee AC and (2) the relationship between PSS and AC mediated by experienced positive relationship with peers. It is in line with previous studies arguing for the effects that CV has on intraorganizational relations (Boštjančič et al ., 2018; Glińska-Neweś et al ., 2019; Haski-Leventhal et al ., 2019; Brzustewicz, 2020) and AC (Brockner et al ., 2014; Haski-Leventhal et al ., 2019). We add to this literature by showing that employees' participation in CV strengthens the effect that PSS and positive relationships with peers have on AC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We show that participation in CV moderates: (1) the link between experienced positive relationships with peers and employee AC and (2) the relationship between PSS and AC mediated by experienced positive relationship with peers. It is in line with previous studies arguing for the effects that CV has on intraorganizational relations (Boštjančič et al ., 2018; Glińska-Neweś et al ., 2019; Haski-Leventhal et al ., 2019; Brzustewicz, 2020) and AC (Brockner et al ., 2014; Haski-Leventhal et al ., 2019). We add to this literature by showing that employees' participation in CV strengthens the effect that PSS and positive relationships with peers have on AC.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research on CV, showing that employees often volunteer both within CV and outside their company (Glińska-Neweś et al ., 2019; Brzustewicz et al ., 2021), in order to capture moderating role of employee participation in volunteering, we proposed a nominal scale, which is a solution used also in other studies on CV (e.g., Rodell et al ., 2017). Our scale of employee participation in volunteering (PV) included:employee participates in volunteering organized in the company he/she works in now (“PV in company”);employee participates in volunteering organized outside the company he/she works in now (“PV outside company”);employee does not participate in any kind of volunteering (“No PV”);employee participates in volunteering organized both in and outside the company he/she works in now (“PV in and outside company”).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review revealed that erstwhile scholars had used varied theoretical perspectives to explain how CSR fosters MW and favorable employee outcomes. The major theories included – sensemaking/meaningfulness theory (Seivwright and Unsworth, 2016; Zhu, 2018; Kim et al , 2018b; Aguinis and Glavas, 2019; Sun et al , 2019; Lysova et al , 2019; Babu et al , 2020; Nazir and Islam, 2020; Sawmong, 2020; Nazir et al , 2021), self-determination/needs-based view (Wiedemann, 2019; Grabner-Kräuter et al , 2020; Nazir et al , 2021), conservation of resources (COR; Xue et al , 2018; Yan et al , 2021; Liu et al , 2021; Luu, 2021), job design/job characteristics theory (Hackman and Oldham, 1975; Pajo and Lee, 2011; Lavine, 2014; Raub and Blunschi, 2014; Ong et al , 2018; Glińska-Neweś et al , 2020), SIT/organizational identification theory (George, 2014; Kim, 2018a; Rodrigo et al , 2019; Chaudhary and Akhouri, 2019; Supanti and Butcher, 2019; Brieger et al , 2020; Chaudhary, 2020; Nazir and Islam, 2020; Afsar et al , 2020; Sawmong, 2020; Wiefek and Heinitz, 2021), SET (Kim et al , 2018b; Supanti and Butcher, 2019; Brieger et al , 2020; Nazir et al , 2021; Luu, 2021), signaling theory (Raub and Blunschi, 2014; Burbano, 2016; Wiefek and Heinitz, 2021), justice-based view (Glavas and Kelley, 2014; Chaudhary, 2019; Supanti and Butcher, 2019; Lythreatis, 2020) and attribution theory (Zhu, 2018; Chaudhary, 2020; Babu et al , 2020).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%